2017
DOI: 10.1038/s41598-017-03642-8
|View full text |Cite
|
Sign up to set email alerts
|

‘Candidatus Cochliophilus cryoturris’ (Coxiellaceae), a symbiont of the testate amoeba Cochliopodium minus

Abstract: Free-living amoebae are well known for their role in controlling microbial community composition through grazing, but some groups, namely Acanthamoeba species, also frequently serve as hosts for bacterial symbionts. Here we report the first identification of a bacterial symbiont in the testate amoeba Cochliopodium. The amoeba was isolated from a cooling tower water sample and identified as C. minus. Fluorescence in situ hybridization and transmission electron microscopy revealed intracellular symbionts located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 69 publications
0
12
0
Order By: Relevance
“…The routine co‐amplification of 18S sequences from marine fungi and nematodes suggest that these associations may be ubiquitous and ecologically important in marine environments; however, further work is needed to determine whether these reported nematode–fungal associations are reflective of symbiosis or parasitism or simply reflect partially digested food present in the nematode gut. Putative parasite species included bacterial taxa such as Rickettsiales (pathogens or endosymbionts of eukaryotic cells; Leclerque, ; Zhalnina et al., ), Rickettsiella (intracellular pathogen of arthropods; Yu & Walker, ), Coxiellaceae (Gammaproteobacteria species that include intracellular parasites in diverse taxa such as insects and mammals and bacterial symbionts of amoebae; Lory, ; Tsao et al., ), fungal taxa such as Tremellales (fungal parasites of other fungi; Findley et al., ), Clonostachys rosea (mycoparasites of fungi and nematodes; Toledo, Virla, Humber, Paradell, & Lastra, ) and enigmatic eukaryote lineages whose phylogenetic placement has not been fully resolved such as Thraustochytriaceae/Aplanochytrium (parasitic or commensal taxa within the Labyrinthulomycota; Moro, Negrisolo, Callegaro, & Andreoli, ). None of these putative parasites had previously been reported from nematode hosts, with the exception of Clonostachys rosea which is a known pathogen of terrestrial nematodes such as Heterodera spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The routine co‐amplification of 18S sequences from marine fungi and nematodes suggest that these associations may be ubiquitous and ecologically important in marine environments; however, further work is needed to determine whether these reported nematode–fungal associations are reflective of symbiosis or parasitism or simply reflect partially digested food present in the nematode gut. Putative parasite species included bacterial taxa such as Rickettsiales (pathogens or endosymbionts of eukaryotic cells; Leclerque, ; Zhalnina et al., ), Rickettsiella (intracellular pathogen of arthropods; Yu & Walker, ), Coxiellaceae (Gammaproteobacteria species that include intracellular parasites in diverse taxa such as insects and mammals and bacterial symbionts of amoebae; Lory, ; Tsao et al., ), fungal taxa such as Tremellales (fungal parasites of other fungi; Findley et al., ), Clonostachys rosea (mycoparasites of fungi and nematodes; Toledo, Virla, Humber, Paradell, & Lastra, ) and enigmatic eukaryote lineages whose phylogenetic placement has not been fully resolved such as Thraustochytriaceae/Aplanochytrium (parasitic or commensal taxa within the Labyrinthulomycota; Moro, Negrisolo, Callegaro, & Andreoli, ). None of these putative parasites had previously been reported from nematode hosts, with the exception of Clonostachys rosea which is a known pathogen of terrestrial nematodes such as Heterodera spp.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these reported taxa are known to parasitize a variety of marine invertebrate species (e.g., Coxiellaceae and Labyrinthulomycetes; Lory, ; Raghukumar, ; Raghukumar & Damare, ). Interestingly, the three bacterial groups Rickettsiella , Rickettsiales and Coxiellaceae appear to represent intracellular pathogens and endosymbionts of eukaryotic cells (previously reported from arthropods and amoebae; Leclerque, ; Tsao et al., ; Yu & Walker, ; Zhalnina et al., ); it is unclear whether these intracellular pathogens/symbionts were derived from prey species or nematode host cells themselves. Overall, our data emphasizes the sheer paucity of knowledge regarding the breadth of parasitic interactions and symbiotic/commensal relationships in marine sediment habitats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Allovahlkampfia which have been suggested to act as hosts for pathogenic bacteria (Mohamed and Huseein, 2016), were also represented in our networks. In this respect, we have recently isolated from the water sample of the tower CT-1 the first testate amoeba, Cochliopodium minus, containing a bacterial symbiont (Tsao et al., 2017). Taken together, our co-presence network analysis recovered a large number of known bacteria-protist interactions and suggested that such relationships are much more diverse than recognized currently.…”
Section: Resultsmentioning
confidence: 99%
“… 2016 ) and ‘ Candidatus Cochliophilus’ (Tsao et al . 2017 ) . Diplorickettsia massiliensis (Subramanian et al .…”
Section: Introductionmentioning
confidence: 99%